Implementation of Three-Step Interview in Speaking Class - Sari, Rai Dewi Riana; Krismayani, Ni Wayan; Gana Kumara, Dewa Gede Agung (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2024)
The purpose of the current study was to determine how to use a Three-Step Interview as a teaching method to help the eighth-grade students at SMPN 5 Mengwi in the academic year 2023/2024 enhance their speaking abilities. The Three-Step Interview helped the students improve their speaking skills while gaining insight from their peers' thoughts and viewpoints. This study focused on 32 students, 14 of whom were male and 18 of whom were female. Action research in the classroom was used to design this study. The researchers completed two cycles to carry out the investigation. The test and questionnaire that the individuals were given served as the source of the study's data, which was qualitatively examined. The study's findings demonstrated a noteworthy enhancement in the participants' ability to carry out a brief conversation. Furthermore, the pre-cycle mean score was 56.88, the cycle I mean score was 73.28, and the cycle II mean score was 83.16. Additionally, the questionnaire demonstrated that the participants responded favourably to the Three-Step Interview during the learning process.